Comparison of Host Cytokine Response in Piglets Infected With Toxigenic and Non-toxigenic Staphylococcus hyicus - Li, Yan; Gou, Hongchao; Chu, Pinpin; Zhang, Kunli; Jiang, Zhiyong; Cai, Rujian; Song, Shuai; Bian, Zhibiao; Li, Chunling (Frontiers in Veterinary Science, 2021)
Staphylococcus hyicus is the most common causative agent of exudative epidermitis (EE) in piglets. Staphylococcus hyicus can be grouped into toxigenic and non-toxigenic strains based on its ability to cause EE in pigs. However, the cytokine response of piglets infected with toxigenic and non-toxigenic S. hyicus has not been completely elucidated. In this study, we evaluated the serum cytokine profile in piglets inoculated with toxigenic and non-toxigenic S. hyicus strains (ZC-4 and CF-1, respectively) using the cytokine array and recorded the clinical signs in piglets. Piglets infected with ZC-4 showed more severe clinical signs and higher mortality than those infected with CF-1. Piglets infected with toxigenic and non-toxigenic S. hyicus strains showed differential cytokine expression; the serum levels of four cytokines (interleukin [IL]-1β, IL-8, IL-12, and IL-10) changed significantly in S. hyicus-infected piglets, and increased IL-10 expression and reduced IL-12 expression was observed only in piglets with toxigenic ZC-4 infection. The toxigenic S. hyicus strain induced a predominantly anti-inflammatory response, and the elevated serum IL-10 may be associated with the severe clinical signs and increased mortality and may be the key cytokine responsible for S. hyicus pathogenicity. Thus, IL-1β, IL-8, IL-12, and, in particular, IL-10 can be considered important biomarkers for toxigenic S. hyicus infection.